The influence of weakly s-permutably embedded subgroups on the p-nilpotency of finite groups - Changwen Li (Algebra and Discrete Mathematics, 2011)
The research was partly supported by the NSF of China (grant no. 11071229) andthe NSF of the Jiangsu Higher Education Institutions (grant no. 10KJD110004).